Law versus Cybercrime - Luis Cordova, José Grabiel; Correa Álvarez, Pascual Felipe; Echerri Ferrandiz, Fernando de Jesús; Pérez Bravo, Julio César (My University, 2017)
Nowadays, Cybercrime is one of the most dangerous and harmful of crimes. States must improve their fighting strategies against this phenomenon in order to protect society and its own integrity. This research, entitled “Law vs Cybercrime” aims to systematize the proceedings for confronting Cybercrime in modern legal systems and to analyze the Cuban legal framework for Cybercrime. This essay analyzes the theoretical and definitional foundations of Cybercrime, the challenges with controlling cybercrime-related acts presents to legal systems, attempts to systematize the proceedings for confronting Cybercrime in modern states legal systems as well as the international legal systems, and finally, analyzes the current Cuban legal regulations against Cybercrime. At the end of the essay can be found the conclusions according to the objectives of this investigation.
Keywords: Cybercrime; Criminal Law; Crime; Cybersecurity; Cyberspace